Integrating communication and collaboration: a study of Kansas water scientists and interdisciplinary teams - Donaldson, Rebecca Erin (My University, 2025)
Water scarcity is a growing global concern, and in Kansas, issues such as limited precipitation and increasing pressure on both surface and groundwater resources have made water research and management a critical priority. Because agriculture accounts for most water use in the state, effective communication from scientists is crucial for supporting informed decision-making among issue holders. The following studies explored how Kansas water science experts communicate their findings and efforts to public audiences, as well as how an interdisciplinary water research team engages in collaborative, transdisciplinary work. This thesis consisted of two qualitative studies. In Study 1, semi-structured interviews were conducted with 21 water science experts across Kansas to identify communication practices, challenges, and perceptions. Findings from this phase informed Study 2, a case study exploring how members of the Kansas Water Institute (KWI) collaborate, exchange knowledge, and engage with issue holders. The case study included nine individual interviews and a focus group that incorporated a visual network mapping activity to better understand team and issue holder relationships. Results indicated that while many water science experts lack formal communication training, they actively adapt and “figure out how to get it done” through experience and collaboration. Their audiences span a diverse range of groups, including producers, policymakers, and the public. The water industry itself is inherently interdisciplinary, and the KWI team was intentionally assembled by the institute’s leadership based on complementary skills and team dynamics. Participants identified barriers to communication and collaboration at internal, external, and structural levels, but also emphasized the importance of leadership and interpersonal relationships in supporting networking and team success. Findings suggest that the water science industry could benefit from increased emphasis on science communication training to strengthen outreach and public engagement. Future interdisciplinary research teams should prioritize intentional formation and collaboration strategies. Additionally, future research could expand on visual methods for mapping social networks and examine how experts’ perceptions of water issues influence their communication priorities and strategies.
Keywords: Water science; Natural resources; Collaboration; Interdisciplinary; Science communication